Pembelajaran Dalam Jaringan di Bidang Matematika dalam Perspektif Mahasiswa - Nengsih, Retno; Nulhakim, Ade Lukman (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The existence of a widespread and simultaneous virus outbreak in various parts of the world, has an impact on all human activities in various sectors of life. This epidemic demands many changes in all fields, including education. Like it or not, learning that was initially carried out in a real classroom must be carried out online (online). Facing this very drastic change encourages educators and students to continue to adapt and innovate in the use of various digital-based learning methods. The need to know the perceptions of students in learning mathematics is very important. Through this, educators can evaluate the learning process that has taken place and elaborate on students better. Moreover, mathematics is a science that will continue to develop following the times and technology. This research is a qualitative qualitative research that aims to obtain an overview of students' perceptions of online learning, especially subjects in the field of mathematics. The case study was conducted in the 2021/2022 academic year. The subjects of this study were 2nd year students majoring in informatics engineering at a private university in DKI Jakarta. The results of this study are 94% of students prefer mathematics course lectures that are conducted face-to-face compared to learning through WAG, telegram, LMS, or google classroom. 50% of students who were asked about the difficulty level of learning mathematics courses through video conferencing thought that the difficulties they faced were in accordance with what they imagined. Likewise with the level of difficulty in learning mathematics courses through WAG, google classroom, or telegram, 49% of these students did not feel that learning was more difficult than they imagined. In such conditions, if asked to provide recommendations regarding what online learning media is suitable for mathematics courses, 72% of them recommend video conferencing media which allows lecturers and students to gather and meet in the same online room. After the research was conducted on students' perspectives on online mathematics learning, it was found that the comparison of students with positive and negative perspectives was quite balanced. There are 33 respondents who have a positive perspective. There are 34 respondents who have a negative perspective. Some others, 11 respondents who are neutral towards the learning.The existence of a widespread and simultaneous virus outbreak in various parts of the world, has an impact on all human activities in various sectors of life. This epidemic demands many changes in all fields, including education. Like it or not, learning that was initially carried out in a real classroom must be carried out online (online). Facing this very drastic change encourages educators and students to continue to adapt and innovate in the use of various digital-based learning methods. The need to know the perceptions of students in learning mathematics is very important. Through this, educators can evaluate the learning process that has taken place and elaborate on students better. Moreover, mathematics is a science that will continue to develop following the times and technology. This research is a qualitative qualitative research that aims to obtain an overview of students' perceptions of online learning, especially subjects in the field of mathematics. The case study was conducted in the 2021/2022 academic year. The subjects of this study were 2nd year students majoring in informatics engineering at a private university in DKI Jakarta. The results of this study are 94% of students prefer mathematics course lectures that are conducted face-to-face compared to learning through WAG, telegram, LMS, or google classroom. 50% of students who were asked about the difficulty level of learning mathematics courses through video conferencing thought that the difficulties they faced were in accordance with what they imagined. Likewise with the level of difficulty in learning mathematics courses through WAG, google classroom, or telegram, 49% of these students did not feel that learning was more difficult than they imagined. In such conditions, if asked to provide recommendations regarding what online learning media is suitable for mathematics courses, 72% of them recommend video conferencing media which allows lecturers and students to gather and meet in the same online room. After the research was conducted on students' perspectives on online mathematics learning, it was found that the comparison of students with positive and negative perspectives was quite balanced. There are 33 respondents who have a positive perspective. There are 34 respondents who have a negative perspective. Some others, 11 respondents who are neutral towards the learning.